WAKTU REAKSI DAN AKURASI DALAM PENGENALAN EKSPRESI WAJAH: SEBUAH EKSPERIMEN PSIKOFISIK - Hartanto, Hartanto (Faculty of Psychology, Diponegoro University, 2018)
The recognition of facial expressions is essential in interaction, however it has never been done in research about its response latency and accuracy. This research aims to measure the accuracy and response times (RTs) from Javanese women to recognize the facial expression. Javanese sampel (N=30) was used in this study. Data were analyzed using two-way Anova with R Programming software and experiment was done using Python Programming. The research yielded: 1) Among all, happy and joy have less RTs. However, there is no significant effect between joy and happy; 2) Among the blocks, block two is considered the fastest, which is followed by block three. Priming upward spiral, however more prone than priming downward spiral in the normal sampel; 3) Sad considered being the emotion which is the most accurate-despite having the longest RTs. According to subject, sad expression was influenced by repetitive exposure from social media content. Positive expression is likewise the expression that being hoped in any interaction, deserved to watch and then being responded. Besides, negative emotion has many labels in Javanese custom that prevent them to be regular expression.